A survey on internet of things: privacy with security of sensors and wearable network ip/protocols - Chowdhury, Subrata; P. Mayilvahanan, Dr (International Journal of Engineering and Technology, 2018)
The paper gives the introduction of the IoT, which lay forward the capabilties to detect and link with the world wide web with the con-nectivity to connect this with the physical objects into a cognate systems. On the other hand some severe concers as the part of the IoT, are been highlighted over the passage gateways of critical personal informations relevants to device and personalized privacy.This survey will summerize and tries to highlight the core issues related to the security threats,and the privacy interest of the IoT.Â Â